WOMEN ECONOMIC EMPOWERMENT: CHALLENGES AND OPPORTUNITIES FOR WOMEN ENTREPRENEURS IN THE AGRICULTURE SECTOR OF PAKISTAN - Noor, Ms. Nadia; Hassan, Dr. Sobia; Gull, Ms. Maryam; Ahmed, Ar. Yasmeen (The journal of contemporary issues in business and government, 2022)
The current study aims to highlight the importance of women’s entrepreneurship in the agricultural sector of Pakistan which provides opportunities for rural women for economic empowerment and poverty alleviation.Gender inequality and social and cultural constraints are the main challenges that hinder the economic empowerment and entrepreneurial development of rural women.The social and economic status of women can be improved through the provision of agricultural education and training, micro-financing, agriculture extension services and development of entrepreneurial and leadership capabilities. The development of microenterprises is crucial for improving the economic well-being of rural women and provides employment opportunities for the rural community. Gender inequality should be addressed to uplift the status of rural women and to provide them with basic facilities of education, health and income. At the Government level, legal, social and economic empowerment should be provided through legislation to ensure their access to education and earnings.The government of Pakistan needs to develop a comprehensive and collaborative system to help rural women by providing grants or interest-free or highly subsidized loan products along with basic business running skillsandto better equip them for proper utilization of the loan.